MicroRNA-218 Regulates Signaling Lymphocyte Activation Molecular (SLAM) Mediated Peste des Petits Ruminants Virus Infectivity in Goat Peripheral Blood Mononuclear Cells - Qi, Xuefeng; Wang, Ting; Li, Zhen; Wan, Yangli; Yang, Bo; Zeng, Wei; Zhang, Yanming; Wang, Jingyu (Frontiers in Immunology, 2019)
Peste des petits ruminants virus (PPRV) is an important pathogen that seriously influences the productivity of small ruminants worldwide. SLAM was identified as the primary receptor for PPRV and other Morbilliviruses, although the regulation of SLAM expression is not yet fully understood. In this study, we revealed a novel mechanism by which PPRV upregulates its receptor SLAM expression and thereby benefits its replication via suppressing miR-218, a novel negative miRNA directly targeting SLAM gene. We demonstrated that PPRV infection downregulates miR-218, which in turn enhances SLAM expression on the surface of goat peripheral blood mononuclear cells (PBMCs), thus promoting PPRV replication. Since modulation of SLAM signaling in lymphocytes might mediate the strong immunosuppressive effect characteristic of PPRV, we also examined the effect of SLAM expression on the production of various cytokines by PBMCs in the absence or presence of PPRV. We demonstrated that miR-218-mediated SLAM expression modulates the production of IFN-γ, TNF-α, and IL-10, importantly, these modulatory effects were enhanced in the presence of PPRV infection. Furthermore, our data clearly showed that PPRV H protein is sufficient to regulate miR-218-mediated SLAM expression. Taken together, our results suggest a novel mechanism involving post-transcriptional pathway regulation of SLAM receptor on goat PBMCs during PPRV infection.